The Rotation Technique in the Diwan of Eleven Planets by Mahmoud Darwish (Semantic Statistical Study) - عجيب ميرنا; نمر مصطفى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research deals with the phenomenon of rotation in the Diwan of Eleven Planets by the palestinian poet Mahmoud Darwish, as one of the most important rhythmic techniques that have taken a new concept in modern poetry. The research is based on clarifying the meaning of the concept linguistically and idiomaticallyin past and present. And then it presents the most important patterns of rotation represented by rotation at the level of prosody, rotation at the level of semantics, and then their meeting together. This is done by observing its presence in the studied diwan in an attempt to explore its semantic and aesthetic dimensions.